ESSENTIALS of oral and maxillofacial surgery / editor M. Anthony (Tony) Pogrel, Karl-Erik Kahenberg, Lars Andersson. - Pogrel, M. Anthony; Kahnberg, Karl-Erik (Wiley Blackwell, 2014)
xiv, 385 hlm. : ilus. ; 29 cm [2 eks.]